Case report: Muscular tuberculosis with lower-extremity muscular masses as the initial presentation: Clinicopathological analysis of two cases and review of the literature - Zhu, Xiao-wei; Luan, Xing-hua; Jiang, Kai-li; Zhang, Chao; Liu, Shi-hua; Cao, Li; Zhong, Ping; Liu, Zhi-yan (Frontiers in Medicine, 2023)
Objectives: Tuberculosis (TB) is a public health problem that mostly affects people in developing countries. TB presenting as a soft-tissue mass is rare, usually seen in muscular tuberculosis (MT) patients. Methods: In this study, we present the clinical, radiographic, pathological features of 2 cases and retrospectively evaluated additional 28 patients who were diagnosed with MT. Results: Patients occurred more in males (60.9%) than females (39.1%) with a male: female ratio of 1.6:1. The average age was 38.9 years and 30.1 years, respectively. MT usually present with painful or painless muscular nodules of lower limbs. Imaging findings, including ultrasound, CT and MRI could identify lesions and locate biopsy locations. The most typical histopathological feature of MT is granulomatous inflammation with caseous necrosis and epithelioid granulomata. Acid-fast bacilli stain and polymerase chain reaction (PCR) assays are helpful to identify tubercle bacillus. Conclusion: We described 2 MT cases with lower extremity muscular masses as the initial presentation. Results suggest that muscle biopsy and pathological analysis remain necessary for the diagnosis. Most of patients could be cured with standardized antitubercular therapy.